It could have been much worse: The Minnesota measles outbreak of 2017. Issue 14 (27th March 2018) - Leslie, Timothy F.; Delamater, Paul L.; Yang, Y. Tony
Abstract: In 2017, Minnesota battled its largest measles outbreak in nearly 30 years, with 79 cases, most of them Somali-American children. In this study, we gathered vaccination and enrollment data for incoming kindergarteners in Minnesota over fall 2012–2016 from the Minnesota Department of Health. We also gathered the number of measles cases by county in 2017. We found that MMR coverage has substantial variation across districts and district types. The minimum MMR coverage is 58.3% and the maximum is 100%. Private schools, which represent approximately six percent of Minnesota's kindergarten enrollment, have a substantially lower coverage rate, with an overall coverage of 83.00%. The 2017 outbreak was relatively isolated. However, the MMR coverage data suggests that other communities could have been at risk given their geographic proximity to the outbreak and modest coverage rates.